Green extract rosemary acid as a viscosity-sensitive molecular sensor in liquid systems. Issue 15 (28th March 2023) - Xu, Lingfeng; Peng, Hui; Huang, Yanrong; Huang, Chunfang; Xie, Chengning; He, Genhe
Abstract : Rosemary extract: rosmarinic acid is a natural molecular sensor extracted from rosemary for viscosity detection in liquids through the fluorescence technique. Abstract : The liquid micro-environment plays a momentous role in the regulation of various activities, and the abnormal changes are often closely related to the deterioration phenomena in multiple beverages. The local viscosity fluctuation has long been regarded as a key indicator to reflect the micro-environmental status changes. Herein, we proposed a versatile optical sensor, rosmarinic acid (RA), one kind of green natural product extracted from rosemary, for monitoring liquid micro-environmental viscosity alterations. RA displays a larger Stokes shift (123.8 nm) with narrow-band energy and exhibits wide adaptability, high selectivity, good sensitivity, and excellent photostability in various commercial liquids. When in high viscous media, a bright fluorescent signal of RA is specifically activated, and a high signal-to-noise ratio signal was released (58-fold). With the assistance of the fluorescence analytical technique, we have successfully achieved tracking the viscosity fluctuations during the deterioration stage of liquids via an in situ and visualization method. Our study will spur additional research on the molecular tools extracted from natural products for liquid safety inspection, and a convenient and sustainable application pathway has been established.